The Influence of Padang Ganting Hot Spring Tourism Object Management on the Economy of Nagari Padang Ganting Community, Padang Ganting District, Tanah Datar Regency - andika, Reza nofri; Chandra, Deded (JURNAL BUANA, 2024)
Abstract study aims to obtain data or information and analyze in depth regarding, (1) How does the management of hot spring tourism objects affect the people's economy in Nagari Padang Ganting. (2) What are the socio-economic conditions around the hot spring tourist attraction. (3) How is the absorption of labor around the Padang Ganting hot spring tourist attraction. This type of research is descriptive qualitative. The types of data used are primary and secondary data, the informants in this study are people who live around hot spring tourism objects, and the key information in this research is the tourism object managers, Padang Ganting Sub-District Head and Koto Gadang Hilir Sub-District Head. Data analysis techniques used data reduction and data display as well as data validation techniques using extended participation, persistent observation, triangulation, and peer-checking through discussions. The results of this study indicate that (1) The management of the Padang Ganting Hot Springs tourist attraction is classified, because there is already a management body that has been formed to maximize management and community participation in this tourist attraction to promote tourism objects so that they attract visitors to come to tourist attractions. desert hot springs. (2) the socio-economic conditions around tourist attractions are increasing every year, due to additional income from selling around tourist attractions. (3) absorption of labor in this tourist attraction so that it reduces the unemployment rate for residents around the tourist attraction who do not have jobs.